2010
DOI: 10.1103/physrevlett.105.087203
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetically Spin Polarized Oxygen Observed in MagnetoelectricTbMn2O5

Abstract: We report the direct measurement of antiferromagnetic spin polarization at the oxygen sites in the multiferroic TbMn2O5, through resonant soft x-ray magnetic scattering. This supports recent theoretical models suggesting that the oxygen spin polarization is key to the magnetoelectric coupling mechanism. The spin polarization is observed through a resonantly enhanced diffraction signal at the oxygen K edge at the commensurate antiferromagnetic wavevector. Using the fdmnes code we have accurately reproduced the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 26 publications
9
31
0
Order By: Relevance
“…Our reflectivities show at about 120 K slightly higher than T N , the collective band sharpens by a temperature driven mechanism in which Mn moments develop magnetic long-range order assisting electron correlation and localization. This band profile change might also point to spin polarization hybridization with Mn 3+ ions at the oxygen sites as has been reported for TbMn 2 O 5 [42].…”
Section: ± =mentioning
confidence: 93%
“…Our reflectivities show at about 120 K slightly higher than T N , the collective band sharpens by a temperature driven mechanism in which Mn moments develop magnetic long-range order assisting electron correlation and localization. This band profile change might also point to spin polarization hybridization with Mn 3+ ions at the oxygen sites as has been reported for TbMn 2 O 5 [42].…”
Section: ± =mentioning
confidence: 93%
“…Recently, it has been shown that the induced magnetic moments at the oxygen might be important to understand the multiferroicity in these materials. 21,24 Resonant x-ray diffraction is an elemental sensitive technique that can probe the magnetism of the different elements separately, but information on the different ions is still missing. Another important aspect to understand multiferroics is the interplay between electric fields and the magnetic order, as this represents the magnetoelectric coupling directly.…”
Section: 1516mentioning
confidence: 99%
“…21 Here we have checked for such spin polarization in both Y and Er compounds (RMn 2 O 5 , R=Y,Er) by measuring the commensurate magnetic reflection ( fig. 4.…”
Section: B Energy Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, significant insights have been obtained using RSXD [44][45][46], and RSXD is also an area of active interest for Diamond theorists [47][48][49][50]. A good example is provided by the so-called hexaferrites.…”
Section: (C) Type II Multiferroicsmentioning
confidence: 99%